2023
DOI: 10.5005/jp-journals-10006-2221
|View full text |Cite
|
Sign up to set email alerts
|

The Association of COVID-19 Severity with Laboratory Parameters, Radiologic Findings, Maternal and Neonatal Outcomes in Pregnant Women: A Multicenter Study in Indonesia

Abstract: Objectives: Severe acute respiratory syndrome-coronavirus 2/COVID-19 infection is still a global concern, with pregnant women are considered as vulnerable population. Until now, the characteristics of pregnant women in Indonesia who are infected with COVID-19, as well as pregnancy and neonatal outcomes, are still unknown. This study aims to obtain national data, which are expected to be useful for the prevention and management of COVID-19 in pregnant women in Indonesia. Methods: There were 1,427 patients recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In this study's cases, the use of ventilators failed to reach the expected oxygen saturation minimum target. This indicated that severe lung damage and respiratory failure caused by COVID-19 might eventually become the leading cause of death in all cases (Dewantiningrum et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Maternal Deaths caused by COVID-19 Infection in the First Year of the Pandemic Wave

Muhammad Ilham Aldika Akbar,
Pungky Mulawardhana,
Manggala Pasca Wardhana
et al. 2023
FMI
“…In this study's cases, the use of ventilators failed to reach the expected oxygen saturation minimum target. This indicated that severe lung damage and respiratory failure caused by COVID-19 might eventually become the leading cause of death in all cases (Dewantiningrum et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Six patients were multiparous, with gestational ages of 22-40 weeks during admission. Three patients came to our hospital by themselves, while rest were referred by other hospitals because of worsening conditions during treatment (Dewantiningrum et al 2023) Six patients came with the chief complaint of dyspnea, a respiratory rate of 26-36 breaths/minute, and oxygen saturation in free roam between 50-95%. There were only two patients with fevers (t>37.5°C) during admission.…”
Section: Discussionmentioning
confidence: 99%

Maternal Deaths caused by COVID-19 Infection in the First Year of the Pandemic Wave

Muhammad Ilham Aldika Akbar,
Pungky Mulawardhana,
Manggala Pasca Wardhana
et al. 2023
FMI